1982
DOI: 10.1073/pnas.79.4.1282
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of serum apolipoprotein E metabolism: role of chylomicron metabolism.

Abstract: The mechanism by which high-fat, high-cholesterol diets lower serum apolipoprotein E (apoE) concentration was studied in rats by feeding a single high-fat, high-cholesterol meal and by intravenously infusing chylomicrons containing low and high amounts of cholesterol. Serum apoE concentrations were unchanged 9 hours after an olive oil meal but were decreased by 35% after an olive oil/cholesterol-enriched meal. The decrease in serum apoE concentrations with the olive oil/cholesterol meal was accompanied by a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…227 W.,%;; 11 0-0.-.-than decreased hepatic synthesis. In support of this concept are data showing that a single feeding of the same cholesterol-rich diet used in our study, rapidly (within 9 h) decreased the serum concentration of apolipoprotein E by 35% (DeLamatre et al, 1982). These results were interpreted by DeLamatre and co-workers to indicate that cholesterol-rich chylomicrons associate with serum apolipoprotein E and the complexed apolipoprotein E is selectively removed via the hepatic chylomicron receptor.…”
Section: Discussionsupporting
confidence: 85%
“…227 W.,%;; 11 0-0.-.-than decreased hepatic synthesis. In support of this concept are data showing that a single feeding of the same cholesterol-rich diet used in our study, rapidly (within 9 h) decreased the serum concentration of apolipoprotein E by 35% (DeLamatre et al, 1982). These results were interpreted by DeLamatre and co-workers to indicate that cholesterol-rich chylomicrons associate with serum apolipoprotein E and the complexed apolipoprotein E is selectively removed via the hepatic chylomicron receptor.…”
Section: Discussionsupporting
confidence: 85%
“…55 Furthermore, high-lipid food intake was reported to result in the production of more CMs; thus, more CMassociated apoE was absorbed by the liver and removed from the serum. 55 The pork group exposed to the PFAAs showed that the level of apoE decreased the most relative to water (28.4%). Since the cholesterol in the liver can be recovered almost completely, 55 its concentration was measured to indicate the amount of CMs absorbed in mouse liver.…”
Section: ■ Materials and Methodsmentioning
confidence: 91%
“…54 ApoE is important in lipoprotein recognition and is also one of the hepatic recognition sites on CM remnants. 55 Thus, the concentration of apoE in mouse blood may reflect the content of CM remnants. As shown in Figure 4f, the level of apoE in all the exposure groups was significantly higher than that in the control group.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Al though both diets induced hypercholesterol emia, as previously reported [ 15], the most impressive difference was seen for the (HDL|-rich) LDL2 fraction since a distinct LDL2 peak appeared after cystine feeding whereas the shoulder existing at the same density for control rats disappeared after cholesterol feeding. The elevation of the TRL level after cholesterol feeding is well known, whereas the decrease in the HDL| level has only been mentioned by some au thors [22,23]. It is noteworthy that hyper cholesterolemia induced in rats by a choles terol-enriched diet containing propylthio uracil is associated with a high level of large apoE-rich HDL [24,25], but this effect is probably due to hypothyroidism induced by the drug [26,27], Therefore in the conditions of the present study, the change in the HDL, level after cholesterol feeding (without pro pylthiouracil) strongly contrasts with that observed after cystine feeding.…”
Section: Discussionmentioning
confidence: 99%